Iranian journal of biotechnology - National Research Center for Genetic Engineering and Biotechnology (Iran) (National Research Center for Genetic Engineering and Biotechnology, 2003)
IJB publishes original scientific research papers in the broad area of Biotechnology such as: Environmental Biotechnology, Medical Biotechnology, Animal Biotechnology, Stem Cell Technology, Marine Biotechnology, Molecular Biotechnology, Nano Biotechnology, Agricultural Biotechnology, Bio-informatics, Food Chain Biotechnology, Industrial and Applied Microbiology and Tissue Engineering.
Keywords: Biotechnology : Periodicals; Biotechnology; Iran